Keputusan Manajerial, Pengungkapan Emisi Karbon, dan Nilai Perusahaan: Peran Kualitas Audit - Fitri Dwi Anggraeni; Novi Darmayanti; Isnaini Anniswati Rosyida (Politeknik Ganesha Medan, 2026)
This study aims to examine the effect of managerial decisions and carbon emission disclosure on firm value, with audit quality as a moderating variable in Basic Materials sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study is motivated by the increasing importance of environmental issues and corporate transparency in influencing investor assessments. Using purposive sampling, this study obtained a sample of 11 firms and employed secondary data from annual reports and sustainability reports. Data were analyzed using Moderated Regression Analysis (MRA) with EViews 14. The results show that managerial decisions have a significant effect on firm value, supporting signaling theory which suggests that investment decisions act as positive signals regarding future growth prospects. In contrast, carbon emission disclosure does not significantly affect firm value, indicating that, in line with stakeholder theory, environmental information has not yet become a primary consideration for investors in emerging markets. Furthermore, audit quality strengthens the relationship between managerial decisions and firm value, consistent with agency theory, as high-quality audits enhance information credibility and reduce information asymmetry. However, audit quality does not moderate the relationship between carbon emission disclosure and firm value, suggesting that the credibility of non-financial information is still limited. Overall, these findings indicate that internal factors, particularly managerial decisions and audit quality, play a more dominant role in determining firm value than environmental disclosure.